DETERMINASI EFISIENSI SEKTOR PUBLIK DALAM PEMBANGUNAN EKONOMI DI PROVINSI JAWA TIMUR - Jauhar Fikrinanda Rahmadi; Parikesit Penangsang (CV. Denasya Smart Publisher, 2024)
Regional income is an input in economic development. This sector includes local original income, balancing funds, and other legitimate income which is used as regional government capital in an effort to improve better regional economic development. This research aims to analyze the efficiency of the public sector, namely district/city regional income in East Java Province which consists of local original income (PAD), balancing funds, and other legitimate income as input variables in efforts to carry out economic development as seen from GRDP, HDI, and the number of people who are not poor as output variables for indicators of regional economic development. The results of this research are that there are five regions in East Java Province in 2017-2021 that are efficient, namely Bojonegoro Regency, Gresik Regency, Pasuruan Regency, Kediri City, and Surabaya City, while in 2020 there are six efficient regions, an increase of one other area, namely Regency Banyuwangi, which achieved a relative efficiency level of 100%, is apart from the five regions which were previously efficient in using input to produce output based on analysis using the Data Envelopment Analysis (DEA) method.